A Reactive Decision-Making Approach to Reduce Instability in a Master Production Schedule - Parada-Daza, V (Taylor and Francis Ltd., 2016)
One of the primary factors that impact the master production scheduling performance is demand fluctuation, which leads to frequently updated decisions, thereby causing instability. Consequently, global cost deteriorates, and productivity decreases. A reactive approach based on parametric mixed-integer programming (MIP) is proposed that aims to provide a set of plans such that a compromise between production cost and production stability is ensured. Several stability measures and their corresponding MIP model are proposed. An experimental study is performed to highlight the effectiveness of the reactive approach with regard to the proposed performance measures. It is observed that an improvement in stability does not mean a significant increase in the total production cost. Furthermore, the procedure yields a set of plans that in practice would enable flexible management of production. © 2015 Taylor & Francis.
Keywords: production planning and control; stability; mixed-integer programming; manufacturing systems; master production schedule